Landscape context of plantation forests in the conservation of tropical mammals - Begotti, Rodrigo Anzolin [UNESP]; Pacífico, Eduardo dos Santos; Ferraz, Silvio Frosini de Barros; Galetti, Mauro [UNESP] (Elsevier, 2018)
Plantation forests have been expanding in many tropical and subtropical environments. Howerver, even when they replace less wildlife friendly land uses such as pastures and annual crops, the biodiversity levels of pristine natural habitats often have not been recovered. Here we addressed how the landscape context of plantation forests located in South-eastern Brazil affects species richness and community resilience of medium and large size mammals. The area covered by native habitat fragments surrounding plantation forests is positively related to functional richness, including the presence of species more vulnerable to extinction in fragmented landscapes. In addition, the degree of aggregation of plantation forest stands is negatively related to more vulnerable species. No primates were recorded in our seven plantation forest sites (ranging from 272 to 24,921 ha), even when they were seen in native habitat fragments adjacent to commercial tree stands. Two invasive species (Sus scrofa and Lepus capensis) were recorded in four plantation forest sites. The impoverishment of fauna in plantation forests is due to two factors. First, plantation forests generally are structurally simplified habitats when compared to highly diverse tropical forests. Secondly, the isolation from habitat fragments which act as source of individuals in the landscape precludes the establishment of individual in plantation forest. We also highlighted the management practices to improve the complexity of vegetation in commercial tree stands should be taken cautiously, insofar as reduced productivity per area entails a greater demand for land. Thus, an alternative would be intensify the management of the commercial tree stands for wood production together with the restoration of adjacent areas set aside to conservation and native habitat fragments protection.
Keywords: Atlantic forest; Eucalyptus; Habitat fragmentation; Pinus; Plantation forest; Wildlife-friendly